Study Quantitative Measures of Pearl Oyster Pinctada radiata (Leach,1814) and Determination of Spatial Distribution Pattern in Lattakia Shore - حسن, نضال (Latakia University Journal -Biological Sciences Series, 2021)
The research dealt, with the study of biomass and abundance of pearl oyster Pinctada radiata in littoral zone in addition to determining the pattern of their spatial distribution, whether it is random, uniform or aggregation. The results showed that the highest value of biomass (± standard deviation) was 1166.10 (77.64 ±) g/m2 during September, and the abundance of individuals was 155.33 (12.50 ±)individual/m2, while the lowest value of biomass was during June, as it reached486.96 (40.20 ±) g/m2 and an abundance of 76.33 (8.33 ±) individual/m2. The relationship between biomass and abundance was positive, very strong, and significant, while the relationship between biomass and total weight was weak, and not significant. The spatial distribution of pearl oyster P. radiata showed a pattern aggregate type in all the studied points.